Productivity and quality enhancement in fodder maize (Zea mays) cultivars through nutrient management strategies - KUMAR, DINESH; SINGH, MAGAN; KUMAR, SANJEEV; MEENA, RAJESH KUMAR; YADAV, MALU RAM; MAKARANA, GOVIND; KUSHWAHA, MANISH; DUTTA, SUSANTA; KUMAR, RAKESH; RAJESH, RAJESH (The Indian Journal of Agricultural Sciences, 2022)
The present study has been carried out in kharif 2018 and 2019 at ICAR- National Dairy Research Institute, Karnal, with three maize (Zea mays L.) cultivars (V1: African Tall, V2: J-1006; V3: P-3396) and four nutrient management strategies (N0: Control; N1: 100% RDF; N2: 75% RDF + PGPR + Panchagavya spray; N3: 50% RDF + 25% FYM + PGPR + Panchagavya spray) using split plot design. Results revealed that maize cv. J-1006 and African Tall produced significantly high and low dry fodder yield, respectively. Significantly high crude protein (CP), ether extracts (EE) and total ash (TA) yields were recorded with J-1006 during both years. In comparison of nutrient management strategies, the application of 75% RDF + PGPR + Panchagavya spray (N2) recorded significantly high dry fodder, CP, EE and TA yields. The foliar spray of Panchagavya along with reduced dose of chemical fertilizers, PGPR and/ or FYM (N2 and N3) to fodder maize significantly reduced the fibre fractions and improved the nutritive values/ energy (DMI, DMD, TDN and NEl). Our results suggest that selection of J-1006 cultivar and application of 75% RDF + PGPR + Panchagavya spray (N2) enhances fodder productivity, quality and reduces the fibre fractions.